UJI BEBERAPA DOSIS ASAP CAIR TANDAN KOSONG KELAPA SAWIT pada BIBIT KELAPA SAWIT (Elaeis Guineensis Jacq) - Siska Evriyanti Lubis; Sampoerno '; M.Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Plant oil palm (Elaeis guineensis Jacq) is a plant that is a top priority in Indonesian plantations. Liquid smoke is a liquid organic fertilizer made ​​by using waste oil palm empty fruit bunches (TKKS). This study aims to examine the use of multiple doses of Liquid Smoke oil palm empty fruit bunches and determine dose tested for the growth of oil palm seedlings. This research has been carried out in the garden experiment Faculty of Agriculture, University of Riau, Jalan Bina Widya, New Simpang Village, District Handsome. This research was conducted with completely randomized design (CRD) consisting of 7 treatments and 3 replications. The data obtained were analyzed statistically by analysis of variance and then proceed to test Duncans New Multiple Range Test (DNMRT) at the level of 5%. Parameters measured were high pertambahn seedlings (cm), in the number of leaves (blade), added girth seed weevil (cm), dry weight (g), the ratio of crown roots, seed quality index. The results showed that administration of 150 ml of liquid smoke TKKS / polybag shows the effect of the increase in plant height, plant dry weight in plants in Main aunt palm nursery. Keyword : Oil Palm, Liquid Smoke, Doses